Efektivitas Daun Kelor Terhadap Kadar Kadmium Dan LDL Kolesterol Dalam Darah Sebagai Indikator Penyempitan Pembuluh Darah (Aterosklerosis) Pada Tikus Putih Yang Terpapar Asap Rokok - Rahayuningsih, Christ Kartika; Agustin, Riya (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2023)
Tobacco consumption in Indonesia is a health epidemic that has direct or indirect toxicity due to exposure of cigarette smoke which contains harmful substances, especially cadmium metal. Cadmium’s exposure can increase the risk of coronary heart disease due to increased LDL cholesterol. One of the cadmium toxicity treatment by utilizing Moringa oleifera leaves as a natural antioxidant considering the flavonoids, saponins, ascorbic acid, carotenoids, phenolics, interquinones as cadmium chelating agents and β-sitosterol content. Therefore, it was necessary to determine the effectiveness of Moringa leaves extract in lowering blood cadmium and LDL cholesterol levels as indicators of atherosclerosis in white rats exposed to cigarettes smoke. The type of research was an experiment with quantitative analysis, conducted at the nutrition laboratory of the Faculty of Public Health Airlangga University and the clinical chemistry laboratory of Surabaya Health Polytechnic in March-July 2023. The independent variable was the doses of Moringa leaf extracts, while the dependent variables were blood cadmium and LDL cholesterol levels of white rats. The analysis of blood cadmium levels used an atomic absorption spectrophotometer and used precipitation methods by a photometer for LDL cholesterol levels. Based on statistical analysis using one way anova showed that blood cadmium levels had a significant value of < 0.05, followed by post hoc tests it was found that treatment group 2 had significant differences from normal groups. Moringa leaves extract dose of 1500 mg/kgbw has been effective in lowering cadmium and LDL cholesterol levels against the risk of atherosclerosis for 14 days. Keywords : Atomic Absorption Spectrophotometry, Cadmium, LDL Cholesterol, Moringa oleifera, photometer, Rattus norvegicus